1982
DOI: 10.3382/ps.0610478
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Sodium Selenite and Selenomethionine upon Nutritional Muscular Dystrophy, Selenium-Dependent Glutathione Peroxidase, and Tissue Selenium Concentrations of Turkey Poults

Abstract: Day-old poults from hens depleted of Se were fed low-Se basal diets (containing corn, soybean meal, and torula yeast but no added vitamin E) with graded levels of Se supplied by Na2SeO3 or seleno-DL-methionine for 28 and 35 days in Experiments 1 and 2, respectively. Adding .04 ppm Se to the basal diet significantly increased body weight and reduced both the incidence of gizzard myopathy and plasma glutamic-oxaloacetic transaminase (PGOT) activity. Further plasma Se and Se-dependent glutathione peroxidase (SeGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
35
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 17 publications
13
35
1
1
Order By: Relevance
“…It was probably caused by differences in metabolic pathways (Forstrom et al, 1978). The observed differences in GSH-Px activity in our study are in agreement with results published by other authors (Cantor et al, 1982;Hassan et al, 1988;Spears et al, 2003;Dlouhá et al, 2008), who found that selenium supplementation increased GSH-Px activity. In addition, GSH-Px activity was significantly higher in the case of using SS in comparison with SCH.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It was probably caused by differences in metabolic pathways (Forstrom et al, 1978). The observed differences in GSH-Px activity in our study are in agreement with results published by other authors (Cantor et al, 1982;Hassan et al, 1988;Spears et al, 2003;Dlouhá et al, 2008), who found that selenium supplementation increased GSH-Px activity. In addition, GSH-Px activity was significantly higher in the case of using SS in comparison with SCH.…”
Section: Discussionsupporting
confidence: 83%
“…Inconsistent results were also obtained for selenium deposition in poultry meat after SS addition. Our results correspond with the findings of some authors (Cantor et al, 1982;Payne and Southern, 2005;Ševčíková et al, 2006;Dlouhá et al, 2008;Skřivan et al, 2008a,b), who showed an increase in selenium in the breast meat of poultry fed selenomethionine, SCH and selenium-enriched yeast. The published results are ambiguous in the case of SS.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, GSH-Px activity in serum and in the studied organs was greatly improved by dietary Se supplementation while the SS group had similar GSH-Px activity in serum, liver and kidney like the Se-Met group but higher in pancreas and breast muscle than the Se-Met group. These results were consistent with earlier reports of Cantor et al (1975Cantor et al ( , 1982 and Payne and Southern (2005b). Less pronounced increases in GSH-Px activity by supplementation of Se-Met compared to SS are probably due to the fact that Se, regardless of its form, must be converted to Se-Cys before it can be incorporated into the selenoprotein enzyme GSH-Px (Forstrom et al, 1978).…”
Section: Discussionsupporting
confidence: 83%
“…In chickens, Cantor et al (8) reproduced muscular dystrophy through Se-deficient diet with normal vitamin E content. The chickens were hatched from the eggs of breeders, which also received a ration deficient in selenium.…”
Section: Introductionmentioning
confidence: 99%